The psychology of health and well-being in mass gatherings: A review and a research agenda - Nick Hopkins; Stephen Reicher (Springer, 2019)
Mass gatherings bring large numbers of people into physical proximity. Typically, this physical proximity has been assumed to contribute to ill health (e.g., through being stressful, facilitating infection transmission, etc.). In this paper, we add a new dimension to the emerging field of mass gatherings medicine. Drawing on psychological research concerning group processes, we consider the psychological transformations that occur when people become part of a crowd. We then consider how these transformations may have various consequences for health and well-being. Some of these consequences may be positive. For example, a sense of shared identity amongst participants may encourage participants to view others as a source of social support which in turn contributes to a sense of health and well-being. However, some consequences may be negative. Thus, this same sense of shared identity may result in a loss of disgust at the prospect of sharing resources (e.g., drinking utensils) which could, in turn, facilitate infection transmission. These, and related issues, are illustrated with research conducted at the Magh Mela (North India). We conclude with an agenda for future research concerning health practices at mass gatherings.